WOMEN'sS EXISTENCE IN SIBEL ERASLAN'S HAJAR (A Feminism Study) - Entang Mega Pertiwi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
AbstractThis study was aimed to study and explain women's existence and Sibel Eraslan's Hajar novel structure based on feminism literature. This is a qualitative research using content analysis method. The findings in this study include; (1) the building element structure contained in Hajar covering theme, characterization, plot, and background; (2) women's images in Hajar which includes both physical and non-physical images; (3) women's roles in Hajar which correspondents domestic and public roles. The existence theory used to study Hajar was Kiekegaard's existence theory which defines images and roles. The theory was used to analyze the efforts undertaken by women against oppression. The results of this study are expected to be useful in the process of learning language and literature, especially in feminism studies, as to improve learners and readers ability in understanding literary works.Keywords: women, existence, feminism, novel.